POTENSI PROGRAM KAMPUNG IKLIM DI SMA NEGERI 4 KECAMATAN TUALANG KABUPATEN SIAK - Dailiati, Surya; Hernimawati, Hernimawati; sudaryanto, sudaryanto; Kurniady, Endang (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
The Climate Village Program (Proklim) is an environmentally friendly program for nature conservation initiated by the Ministry of Environment and Forestry of the Republic of Indonesia (KLHK RI). This program can be implemented at the Rukun Warga (RW), hamlet, village/kelurahan and school levels. This program prepares communities to be involved in climate resilience and low greenhouse gas (GHG) emissions in their lifestyle. From the results of the field visit, it was discovered that SMA Negeri 4 Tualang did not know and understand the climate village program. However, it has the potential to be empowered and realized as a climate village in the educational environment. The method of implementing community service is carried out by means of discussion. State High School (SMA) 4, Tulang District, Siak Regency is committed to utilizing the environment to support sustainability programs, environmental resilience, especially the climate village program. The school area, which is quite large, has been maintained with various plants which help reduce global warming.